(untitled) (Journal of Rangpur Medical College, 2025)
Background: Preventive health measures play a critical role in reducing the burden on healthcare systems by minimizing avoidable hospital admissions and associated costs. In general medicine, strategies such as vaccinations, lifestyle modifications, and routine health screenings have proven effective in preventing the onset and progression of chronic diseases. Objective: This study explored the impact of various preventive health measures on admission rates. Methods: The study was conducted at National Institute of Neurosciences and Hospital, from July 2023 to July 2024, using a mixed-methods approach to explore the role of preventive health measures in reducing hospital admissions within general medicine. The sample size was 300.The data analysis was performed using SPSS version 26. The methodology was designed to ensure reliability and validity by triangulating data from multiple sources and employing consistent data coding and analysis procedures. Result: The study of 300 patients revealed that preventive health measures significantly reduced hospital admissions and length of stay. Vaccination (66.7%) reduced admissions by 90.0%, lifestyle programs (50.0%) by 80.0%, and routine health checkups (>1, 60.0%) by 88.9%, all with significant p-values. Preventive strategies also lowered average admissions and stay duration: vaccination reduced stays by 40.0%, lifestyle programs by 25.0%, and routine checkups by 42.9%. Key barriers, effectiveness, and awareness gaps were highlighted by healthcare providers. Risk factors like smoking, obesity, and high cholesterol correlated with higher admission rates, emphasizing the need for multifactorial preventive approaches. Conclusion: Preventive health measures significantly reduce hospital admissions, shorten hospital stays, and mitigate the impact of modifiable risk factors. This study’s results reinforce the necessity for robust preventive health systems supported by policy initiatives, public awareness campaigns, and interdisciplinary collaboration. By adopting a proactive approach to health management, healthcare systems can achieve sustainable improvements in patient outcomes and resource efficiency. J Rang Med Col. March 2025; Vol.10, No.1: 63-68